New host, geographical records, and factors affecting the prevalence of helminths infection from synanthropic rodents in Yucatán, Mexico - Panti-May, J. A.; Palomo-Arjona, E.; Gurubel-González, Y.; Torres-Castro, M. A.; Vidal Martínez, V. M.; Machain-Williams, C.; Hernández-Betancourt, S. F.; Robles, Maria del Rosario (Helminthologia)
The aim of this paper was to study the occurrence of helminths in Mus musculus and Rattus rattus from urban, suburban and rural settlements in Yucatán, Mexico; and to analyse the host factors (e.g. sex) related to helminths? distribution. Helminths in a total of 279 rodents were surveyed by visual examination of the liver for metacestodes and faecal examination for helminth eggs using the formalin-ethyl acetate sedimentation technique. The cestodes Hydatigera taeniaeformis (metacestodes detected in the liver) and Hymenolepis diminuta, and the nematodes Aspiculuris sp., Nippostrongylus brasiliensis, Syphacia muris,Syphacia obvelata, and Trichuris muris were identiﬁed. In M.musculus,the prevalence of infection with T.muris and H.taeniaeformis was higher in the rural village compared to those in the suburban neighbourhood. For R.rattus,a higher prevalence of infection with H.diminuta was found in the urban site compared to that in the suburban site. This study reports the occurrence of H.diminuta among rodents living in close proximity to humans, representing a potential public health risk. In addition, this survey increases our understanding of dynamic transmission among intestinal helminths recorded in Yucatán, Mexico. Fil: Panti-May, J. A. Universidad Autonoma de Yucatan; México Fil: Palomo-Arjona, E. Universidad Autonoma de Yucatan; México Fil: Gurubel-González, Y. Universidad Autonoma de Yucatan; México Fil: Torres-Castro, M. A. Universidad Autonoma de Yucatan; México Fil: Vidal Martínez, V. M. Centro de Investigación y de Estudios Avanzados del Instituto Politécnico Nacional México Fil: Machain-Williams, C. Universidad Autonoma de Yucatan; México Fil: Hernández-Betancourt, S. F. Universidad Autonoma de Yucatan; México Fil: Robles, Maria del Rosario. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de ...